Experiments with Marxism-Leninism in Cold War Southeast Asia - Galway, Matthew (Asian Studies Series, 2022)
One of the most contentious theatres of the global conflict between capitalism and communism was Southeast Asia. From the 1920s until the end of the Cold War, the region was racked by international and internal wars that claimed the lives of millions and fundamentally altered societies in the region for generations. Most of the 11 countries that compose Southeast Asia were host to the development of sizable communist parties that actively (and sometimes violently) contested for political power. These parties were the object of fierce repression by European colonial powers, post-independence governments and the United States. Southeast Asia communist parties were also the object of a great deal of analysis both during and after these conflicts. This book brings together a host of expert scholars, many of whom are either Southeast Asia-based or from the countries under analysis, to present the most expansive and comprehensive study to date on ideological and practical experiments with Marxism-Leninism in Southeast Asia. The bulk of this edited volume presents the contents of these revolutionary ideologies on their own terms and their transformations in praxis by using primary source materials that are free of the preconceptions and distortions of counterinsurgent narratives. A unifying strength of this work is its focus on using primary sources in the original languages of the insurgents themselves.